Suboxic Deposition of Ferric Iron by Bacteria in Opposing Gradients of Fe(II) and Oxygen at Circumneutral pH - Sobolev, Dmitri (American Society for Microbiology, 2001)
The influence of lithotrophic Fe(II)-oxidizing bacteria on patterns of ferric oxide deposition in opposing gradients of Fe(II) and O(2) was examined at submillimeter resolution by use of an O(2) microelectrode and diffusion microprobes for iron. In cultures inoculated with lithotrophic Fe(II)-oxidizing bacteria, the majority of Fe(III) deposition occurred below the depth of O(2) penetration. In contrast, Fe(III) deposition in abiotic control cultures occurred entirely within the aerobic zone. The diffusion microprobes revealed the formation of soluble or colloidal Fe(III) compounds during biological Fe(II) oxidation. The presence of mobile Fe(III) in diffusion probes from live cultures was verified by washing the probes in anoxic water, which removed ca. 70% of the Fe(III) content of probes from live cultures but did not alter the Fe(III) content of probes from abiotic controls. Measurements of the amount of Fe(III) oxide deposited in the medium versus the probes indicated that ca. 90% of the Fe(III) deposited in live cultures was formed biologically. Our findings show that bacterial Fe(II) oxidation is likely to generate reactive Fe(III) compounds that can be immediately available for use as electron acceptors for anaerobic respiration and that biological Fe(II) oxidation may thereby promote rapid microscale Fe redox cycling at aerobic-anaerobic interfaces.